Correlation of positron emission tomography/computed tomography scan with smoking, tumor size, stage and differentiation in head and neck cancer patientspositron emission tomography/computed tomography - Pleitz, Jordan; Sinha, Partha; Dressler, Emily; Aouad, Rony (World Journal of Nuclear Medicine, 2017)
The goal of this study was to identify associations between positron emission tomography/computed tomography (PET/CT) maximum standardized uptake value (SUVmax) in patients presenting with head and neck squamous cell carcinoma (SCC) with tumor site, size, histologic differentiation, smoking, and diabetes. Charts of patients with oropharyngeal and laryngeal SCC who underwent 18F-fluorodeoxyglucose PET/CT scans were reviewed between May 2007 and August 2013. Statistical analyses included modeling log-transformed SUVmax values by tumor site, size, histologic differentiation, smoking status, and diabetes using unadjusted linear regressions. Differences were considered statistically significant for P< 0.05. A total of 111 patients (54 with oropharynx and 57 with larynx cancers) were included, 83 men and 28 women with an average age of 57.5 years old. There was a significantly higher pack-year smoking history (P = 0.005) in the larynx cancer group. While tumor T-stage was found to be significantly different (P < 0.0001), there was no difference in tumor size between the two groups: 3.16 cm and 3.58 cm in the oropharynx and larynx, respectively (P = 0.55). In the oropharynx cohort, SUVmax was associated with both tumor size (P = 0.0001) and stage (P < 0.0002). Interestingly, SUVmax differed by tumor differentiation in the larynx (P = 0.04) but not the oropharynx (P = 0.71). Finally, there was no significant difference in SUVmax relative to diabetes and smoking status. PET/CT SUVmax correlated with both tumor size and stage in oropharyngeal cancer patients, and it correlated only with tumor differentiation but not the size or stage in the larynx. There were no significant differences in SUVmax by diabetes or smoking status.
Keywords: Larynx cancer; maximum standardized uptake value; oropharynx cancer; positron emission tomography/computed tomography; smoking; tumor differentiation